The effect of corporate taxes on investment: Evidence from the Colombian firms - Ligia Alba Melo-Becerra; Javier Ávila Mahecha; Jorge Enrique Ramos-Forero (Graduate Institute of International and Development Studies, 2017)
The paper assesses the role of taxes on investment in Colombian firms. The analysis is carried out at the firm level for the period 2003-2014. During this period, the national government set five different tax reforms, including changes in the statutory tax rates, tax credits and incentives for corporate investment. The effect of corporate taxation on investment is estimated by first determining the impact of taxation on the cost of capital by computing the effective marginal tax rates (EMTRs) at firm level. Then, we estimate the impact of the cost of capital on investment through a panel data regression. Endogeneity is controlled by an instrumental variable approach, simulating post-reform effective marginal tax rates under pre-reform firm characteristics. Results are robust with different control variables, although some significant differences by size and economic sector of the firm are found.
Keywords: H32; H25; C23; D22; 330; Corporate taxes; Marginal effective tax rate; Investment; Cash flows